Diversity of Ferns (Pterydophyta) in The Urban Forest of Metro City, Lampung - Anisatu Z Wakhidah; N. Saniah; A. C. Ummah; Anggita Anggita; F. Fauziah (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2026)
Metro City (Lampung, Indonesia) contains five urban forests, including Linara and Tejosari, whose fern (ferns and lycophytes) diversity has not been comprehensively documented. This study inventoried fern species composition, abundance, conservation status, and general ecological roles in both urban forests using a systematic plot approach (four 5 × 5 m plots per site; 100 m² per site). All individuals within plots were recorded and counted; taxa were identified using vegetative characters supported by field photographs, and scientific names were standardized using Plants of the World Online (POWO). Diversity was quantified using the Shannon–Wiener index (H’), and conservation status was checked using the IUCN Red List. A total of 48 species were recorded across both sites; Linara showed higher diversity (H’ = 3.23; high category) than Tejosari (H’ = 2.65; moderate category). The most abundant species differed between sites, with Drymoglossum piloselloides dominating Linara (564 individuals) and Cystopteris fragilis being most frequent in Tejosari (32 individuals). Taxonomically, species richness was concentrated in a few families, especially Polypodiaceae (16 species), while other families contributed fewer species. Differences between sites are indicate that the two locations provide different microhabitat conditions, particularly regarding the availability of shaded and humid areas that support the existence of ferns. The findings of the dominance fern family and differences in the most abundant species in each location confirm that variations in habitat structure and levels of disturbance in urban green spaces have the potential to shape local fern communities. Therefore, urban forest management needs to prioritize the maintenance of key microhabitats and habitat continuity to maintain fern diversity.